Community-based tourism governance and study of the barriers to the consolidation of two communities in Recife (Pernambuco, Brazil) in light of the Governance Analysis Model - Graciano, Pollyanna Fraga; Holanda, Luciana Araújo de (Revista Turismo em Análise, 2021)
Based on a new paradigmatic vision of tourist phenomenon, the Community-Based Tourism (CBT) increases the tourist activity inspired by sustainable development and by the protagonism of local actors, contributing to alternative income generation and improving the quality of life of communities. Despite being constantly studied and debated by the academy, such CBT initiatives face difficulties to consolidate themselves in the tourist market and tend to decline. Research carried out in the field indicates that governance is one of obstacles to consolidation. In the municipality of Recife, two communities, Bomba do Hemetério and Ilha de Deus, develop CBT initiatives but neither was established as a regular tourist destination. Therefore, this study analyzes the governance of Recife CBT initiatives by applying the CBT governance analysis model (GAM), adopting participation, transparency, and effectiveness as constructs. The research is characterized as qualitative, descriptive, and explanatory. The data collection techniques used were observation, document research, and semi-structured interviews. For data analysis, a content analysis by categorization, following lexical criterion was conducted. Among the obstacles to the consolidation of Recife initiatives we highlight the internal conflicts, low relations with public authorities, and high external dependence, including networks.